2019
DOI: 10.1111/nph.15701
|View full text |Cite
|
Sign up to set email alerts
|

Snow algae communities in Antarctica: metabolic and taxonomic composition

Abstract: Summary Snow algae are found in snowfields across cold regions of the planet, forming highly visible red and green patches below and on the snow surface. In Antarctica, they contribute significantly to terrestrial net primary productivity due to the paucity of land plants, but our knowledge of these communities is limited. Here we provide the first description of the metabolic and species diversity of green and red snow algae communities from four locations in Ryder Bay (Adelaide Island, 68°S)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
70
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(76 citation statements)
references
References 84 publications
(129 reference statements)
6
70
0
Order By: Relevance
“…The bacteria that were widespread in our study, all of which had populations larger than the vast majority of detected bacteria, may include mutualist partners of snow algae. Previous work reported many of the same bacterial taxa (Figures 6, 7B and Table 1) and widely distributed OTUs ( Figure 7B) from both polar and alpine snow algae blooms, including Sphingobacteriaceae, Chitonphagaceae, and Cytophagia (Brown et al, 2015;Lutz et al, 2016;Hamilton and Havig, 2017;Terashima et al, 2017;Davey et al, 2019). Various Proteobacteria are also often reported, including Oxalobacteraceae (e.g., Glaciimonas), Comamonadaceae (e.g., Polaromonas), and Pseudomonas (Lutz et al, 2016;Hamilton and Havig, 2017;Terashima et al, 2017;Davey et al, 2019).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…The bacteria that were widespread in our study, all of which had populations larger than the vast majority of detected bacteria, may include mutualist partners of snow algae. Previous work reported many of the same bacterial taxa (Figures 6, 7B and Table 1) and widely distributed OTUs ( Figure 7B) from both polar and alpine snow algae blooms, including Sphingobacteriaceae, Chitonphagaceae, and Cytophagia (Brown et al, 2015;Lutz et al, 2016;Hamilton and Havig, 2017;Terashima et al, 2017;Davey et al, 2019). Various Proteobacteria are also often reported, including Oxalobacteraceae (e.g., Glaciimonas), Comamonadaceae (e.g., Polaromonas), and Pseudomonas (Lutz et al, 2016;Hamilton and Havig, 2017;Terashima et al, 2017;Davey et al, 2019).…”
Section: Discussionmentioning
confidence: 65%
“…These relationships have not been documented in snow algae microbiomes, but there is some evidence for their existence. In a metabolomic study of green snow in Antarctica, Davey et al (2019) found calystegine, an alkaloid noted for plant-bacterial communication. In a laboratory experiment, Terashima et al (2017) showed that a Chloromonas spp.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, green colored snowfields inhabited by C. nivalis are rarely found, because the green, flagellated cells have a very short reproductive phase before they form spores to better resist excessive irradiation, desiccation, low nutrient concentrations, and freeze-thaw cycles [ 48 50 ]. Previous studies have indicated that green and red snowfields might be successive stages [ 51 ]. However, in our study, the green color derived likely from Chloromonas spp.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that ice environments might have huge spatial heterogeneity. Ice masses contain important snow algal communities (Anesio et al, ; Davey et al, ) that might have acted as hosts or sources of necromass for zoosporic ancestors of terrestrial fungi (Kaštovská et al, ; Boetius et al, ; Duran et al, ; Hotaling, Hood & Hamilton, ). Zoosporic fungi can propagate easily through semi‐melted ice surfaces, and even modern icy environments, such as periglaciar soils or arctic seas, contain an unsuspected abundance and diversity of zoosporic lineages (Freeman et al, ; Hassett & Gradinger, ; Rämä et al, ).…”
Section: Down To Earth: Terrestrialization In Fungimentioning
confidence: 99%